2014
DOI: 10.1179/1743282014y.0000000096
|View full text |Cite
|
Sign up to set email alerts
|

Bryophyte photosynthesis in sunflecks: greater relative induction rate than in tracheophytes

Abstract: Bryophyte photosynthesis in sunflecks: greater relative induction rate than in tracheophytes Jiri K u b a s e k 1'2 , T o m a s H a j e k 2,3, J a n ic e M . G lim e 4 1G lobal Change Research Centre, ASCR, Brno, Czech R epublic, d e p a r tm e n t o f E xperim ental Plant Biology, Faculty o f Science, U niversity o f S outh B ohem ia, Branisovska 31, CZ-370 05 Ceske B udejovice , Czech Republic, in s t it u t e o f B otany o f ASCR, D ukelska 135, CZ-379 82 Trebon, Czech Republic, d e p a r tm e n t o f B io … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 47 publications
1
9
0
Order By: Relevance
“…Our data are consistent with the results obtained on other bryophytes in similar micro-climatic conditions in forest communities (Kubasek et al, 2014).…”
Section: Shootssupporting
confidence: 93%
“…Our data are consistent with the results obtained on other bryophytes in similar micro-climatic conditions in forest communities (Kubasek et al, 2014).…”
Section: Shootssupporting
confidence: 93%
“…() found that moderate N deposition levels were associated with increased bryophyte growth, suggesting that nutrient enrichment, even relatively high level, may not always have direct toxic, counterproductive effect on bryophytes. Many bryophytes also show a marked degree of shade tolerance (Marschall & Proctor ; van der Wal, Pearce & Brooker ) and are able to rapidly photosynthesize under light pulses (Kubasek, Hájek & Glime ), thus increasing their opportunities to survive in moderately dense vascular plant understories (created by fertilization alone; Eskelinen & Harrison ) where competition for light is likely to be more intense. Due to their small size and high colonization ability (Vanderpoorten & Goffinet ), bryophytes are likely to survive even in extremely small microhabitats and may be less affected by competition by tall vascular plants.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, erect bryophytes growing in the forest understory must invest a greater proportion of their nitrogen into their chloroplast pigments to improve their light-harvesting abilities and thus offset the effect of self-shading. In contrast, the prostrate species creep along the substrate and their shoot structures are more efficient at collecting the weak light in the forest understory and utilising temporal heterogeneity in light levels (such as sunflecks) (Bates 1998;Kubásek et al 2014;Niinemets and Sack 2006). In summary, the growth form of a bryophyte has a strong effect on its light interception pattern and nutrient distribution, thereby affecting its functional trait relationships.…”
Section: Comparing the Functional Trait Scaling Relationships Betweenmentioning
confidence: 99%